Beyond amylose content, selecting starch traits impacting in vitro α-amylase degradability in a wheat MAGIC population. (1st September 2022) - Wang, Yuzi; Kansou, Kamal; Pritchard, Jenifer; Zwart, Alexander B.; Saulnier, Luc; Ral, Jean-Philippe
Abstract: A major challenge faced when studying the "structure-degradability" interaction of native starch is deciphering the interdependency between different structural levels, especially when experimental conditions limit the number of samples. To tackle this challenge, 224 wheat starches from a 4-way multiparent advanced generation inter-cross population were screened for structural features and degradation profiles by porcine pancreatic α-amylase. A hierarchical clustering on principal components (HCPC) were used as multifactorial analysis to explore the data structure. The degradation procedure was proved to be robust and sensible enough to screen a large collection of starches. The HCPC highlighted the combined effects of granule size distribution (GSD), amylopectin chain length distribution (CLD), amylose content and endogenous α-amylase activity on degradation kinetics. Especially the GSD and amylopectin CLD showed high co-occurrences with specific hydrolysis profiles. These findings provide an innovative screening method and structural factors to be primarily considered for wheat starch selection in breeding programs. Graphical abstract: Unlabelled Image